Alternative causes of bioreaction to prosthetic heart valves: three cases with pannus formation - Süleyman Karakoyun; Ozan Mustafa Gürsoy; Macit Kalçık; Şermin Çoban Kökten; Mehmet Özkan (Türk Kardiyoloji Derneği Arşivi, 2014)
Pannus formation is an infrequent but serious complication of prosthetic heart valve surgery. The cause of pannus is recognized as a bioreaction to the prostheses; histological investigations have shown that pannus comprises collagen and elastic tissues containing endothelial cells, chronic inflammatory cells, and myofibroblasts. However, the detailed mechanism of its formation has not been fully demonstrated. We aimed to evaluate the potential role of vascular endothelial growth factor (VEGF) and matrix metalloproteinase-2 (MMP-2) in the pathogenesis of pannus formation in three patients with mechanical prosthetic heart valves. Pannus specimens removed from the prostheses were fixed in 10% neutral-buffered formalin for 24 hours after surgical removal and paraffin-embedded using standard procedures. Serial sections were cut at 4 μm for immunohistochemistry analysis. Hematoxylin and eosin (HE) was used in the histological analysis. VEGF and MMP- 2 were studied in the immunohistochemistry analysis. Three patients with mechanical prosthetic obstruction due to pannus overgrowth underwent redo valve surgery. In the first and second patients, the mitral prosthesis was explanted along with the pannus overgrowth. The third patient had both aortic and mitral prostheses; the aortic prosthesis was explanted with obstructive pannus formation, whereas the mitral valve was spared with excision of the nonobstructive pannus. The immunohistochemical study demonstrated the expressions of MMP-2 and VEGF in all of the pannus specimens acquired from these cases. VEGF and MMP-2 may play a role in the mechanism of pannus formation as the elements of the chronic active inflammatory process.